2009
DOI: 10.1111/j.1471-4159.2009.06476.x
|View full text |Cite
|
Sign up to set email alerts
|

Pim‐1 kinase as activator of the cell cycle pathway in neuronal death induced by DNA damage

Abstract: DNA damage is a critical component of neuronal death underlying neurodegenerative diseases and injury. Neuronal death evoked by DNA damage is characterized by inappropriate activation of multiple cell cycle components. However, the mechanism regulating this activation is not fully understood. We demonstrated previously that the cell division cycle (Cdc) 25A phosphatase mediates the activation of cyclin‐dependent kinases and neuronal death evoked by the DNA damaging agent camptothecin. We also showed that Cdc25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Cortical neuron cultures were prepared as described before [41], [42]. Briefly, embryos were extracted at 14.5–15.5 days gestation.…”
Section: Methodsmentioning
confidence: 99%
“…Cortical neuron cultures were prepared as described before [41], [42]. Briefly, embryos were extracted at 14.5–15.5 days gestation.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP Assay-CGNs treated with/without hypoxia and reoxygenation were subjected to a ChIP assay as described previously (33). The mouse B-Myb promoter region was amplified using the following primers: 5Ј-CCTCCTCCTTC-TCCTCCTTC-3Ј and 5-CACTATACCCGTGCGCTTCT-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…Mediated by Genotoxic Stress-Aberrant activation of neuronal cell cycle induced by pathologic stress such as DNA damage and ischemic insult is thought to contribute to cell death through regulation of E2F members (7,17,33). However, the relative contribution of different E2F members in neuronal death is not clear.…”
Section: E2f Family Members Differentially Regulate Neuronal Deathmentioning
confidence: 99%
“…In line with our findings, studies in hematopoietic cells and neurons have shown a significant increase in Pim-1 in response to DNA damage contributing to cell survival. 43,44 In addition to miR-204 downregulation, upregulation of Pim-1 in PAH 10 could contribute to the PARP-1-dependent cell survival in PAH-PASMCs. In addition, several recent studies have attributed numerous posttranscriptional functions to PARP proteins, 19 including the regulation of the microRNA binding protein Argonaute 2.…”
Section: Discussionmentioning
confidence: 99%